The social and psychological problems faced by the elderly in Lattakia Governorate - زريقة, يسرى; خضور, حلا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Interest in the psychology of old age has increase in recent times, duo to the increase of elderly people, the increase in cognitive development in the issues of the elderly and their continuous needs and problems, and there are many attempts to define this stage, and several terms have been used that deal with the elderly, whether on the temporal level or from looking at the changes that occur to them in this stage. Starting from this, this study seeks to identify the most important concepts and terms that dealt with the stage of aging and the elderly, and to know the most important characteristics of the elderly at this stage, and then to identify the most general social and psychological needs and problems of the elderly. Where the descriptive approach was adopted to then reach some conclusions, recommendations and proposals to alleviate these problems.